2018
DOI: 10.1093/jn/nxy017
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Urban, but Not Urban, Residence in Bolivia Is Associated with Higher Odds of Co-Occurrence of Overweight and Anemia among Young Children, and of Households with an Overweight Woman and Stunted Child

Abstract: Peri-urban, but not urban, residence in Bolivia is associated with a higher risk of the nutritional double burden than rural areas. Understanding how heterogeneous urban environments influence nutrition outcomes could inform integrated policies that simultaneously address both undernutrition and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…Similarly to other studies in LAC (Jones et al, ; Parra et al, ; Pérez‐Escamilla, Villalpando, Shamah‐Levy, & Méndez‐Gómez Humarán, ), we found that mild food insecurity was associated with a greater risk of the dual burden at the household level. Previous research in LAC and elsewhere has linked HFI to both the dual burden and its components of under‐ and over‐nutrition.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly to other studies in LAC (Jones et al, ; Parra et al, ; Pérez‐Escamilla, Villalpando, Shamah‐Levy, & Méndez‐Gómez Humarán, ), we found that mild food insecurity was associated with a greater risk of the dual burden at the household level. Previous research in LAC and elsewhere has linked HFI to both the dual burden and its components of under‐ and over‐nutrition.…”
Section: Discussionsupporting
confidence: 89%
“…In LMIC, household food insecurity (HFI) has traditionally been associated with inadequate dietary intake, poor diet quality, infection, anemia, and growth faltering in children (Anderson, Tegegn, Tessema, Galea, & Hadley, ; Campbell et al, ; Hackett, Melgar‐Quiñonez, & Álvarez, ; Schmeer & Piperata, ). However, as in high‐income countries, where a large literature links HFI to obesity (eg, Dinour, Bergen, & Yeh, ; Gorton, Bullen, & Mhurchu, ; Seligman, Laraia, & Kushel, ; Townsend, Peerson, Love, Achterberg, & Murphy, ) particularly among women (Martin & Lippert, ), HFI has also been associated with overweight, obesity, and cardiometabolic disease in LMIC (Jones et al, ; Pérez‐Escamilla, Villalpando, Shamah‐Levy, & Méndez‐Gómez Humarán, ). While less research has examined the potential role of HFI in shaping the dual burden of malnutrition (Jones et al, ; Jones, Mundo‐Rosas, Cantoral, & Levy, ), HFI may be particularly important in this context, shaping both food choice and psychological responses to perceived threats of food shortages in ways that may increase the development of obesity and NCD (Seligman, Laraia, & Kushel, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periurban areas surrounding cities like Mexico City, Caracas, Bogota, Rio de Janeiro, Lima, and Sao Paulo, are confronted with violence, poverty, and environmental problems in various degrees (da Gama Torres 2008). Populations in peri-urban areas were associated with the double burden of malnutrition, more than in rural areas, showing overweight and anemia in children, overweight mothers, and stunted children (Jones et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The urban population is increasing day by day with the facilities' and infrastructure's advancement in urban areas [8]. It has an impact, one of which is an increase in nutritional problems, including obesity and malnutrition problems [9]. Obesity and anemia in women of working age (15-49 years) are the nutritional issues in urban areas and malnutrition, especially stunted children aged 6-59 months [10].…”
Section: Introductionmentioning
confidence: 99%